Brain derived neurotrophic factor inhibits apoptosis in enteric glia during gut inflammation - Steinkamp, Martin; Kirsch, Joachim (Medical science monitor, 2012)
Background: Enteric glia cells (EGCs) are essential for the integrity of the bowel. A loss of EGCs leads to a severe inflammation of the intestines. As a diminished EGC network is postulated in Crohn’s disease (CD), we aimed to investigate if EGCs could be a target of apoptosis during inflammation in CD, which can be influenced by Brain derived neurotrophic factor (BDNF). Material/Methods: GFAP, BDNF and cCaspase-3 were detected in the gut of patients with CD. Primary EGC cultures were established and cultivated. Tyrosine receptor kinase (TrkB) receptors on these cells were investigated by western blot and immunofluorescence. Rate of apoptosis was induced by tumor necrosis factor (TNF-alpha) and interferon (IFN-gamma). Apoptosis was determined by a fluorometric caspase 3/7 activation assay after preincubation of these cells with BDNF or neutralizing anti-BDNF antibodies. Results: Mucosal GFAP-positive EGCs undergo apoptosis revealed by cCaspase-3 in the gut of patients with CD expressing BDNF highly. The combination of TNF-alpha and IFN-gamma was able to induce apoptosis in primary EGCs, whereas these factors alone did not. Brain derived neurotrophic factor (BDNF) attenuate glia cell apoptosis to a small extent, but neutralizing antibodies against BDNF dramatically increased apoptosis. Conclusions: Mucosal EGC apoptosis is an important finding in the gut of patients with CD. Proinflammatory cytokines, which are highly increased in CD, induce EGC apoptosis, whereas the neurotrophin BDNF might be protective for EGC. Since EGCs are implicated in the maintenance of the enteric mucosal integrity, EGC apoptosis may contribute to the pathophysiological changes in CD.